Standardization of gum tapping techniques for Butea monosperma L.: Effect of types and depth of incision on gum exudation - Prasad, Rajendra; Singh, Prashant; Tripathi, V.D.; Shukla, Ashok; Handa, A.K.; Alam, B.; Singh, R.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
Butea monosperma L. is an important multipurpose deciduous tree species of India. It is mainly distributed in arid and semi-arid areas of the country. Gum of this plant called ‘kamarkas’ is widely used in pharmacological industry. In Bundelkhand region of Central India, the Saharia tribe exploits B. monosperma for gum exudation. They generally tap the tree by making deep incisions on stem-bark, which affects tree health. Therefore, a study was carried out to test the effects of different types of incisions/ cuts (knotching, horizontal, vertical and slant cuts); depths of incisions (0.5, 1.0 and 1.5 cm deep cut) and lengths of incisions (1.0, 2.0 and 3.0 cm long cut) marked on stem-bark of B. monosperma to exude gum-butea and its yield. Significantly higher gum-butea was collected from knotching (conventional method), followed by vertical cut treatment. Among various treatments of depths and lengths of cuts, 1.0 cm deep cut and 1.0 cm long cut gave higher yield of gum-butea than the other depths and lengths of incisions. Thus, it may be concluded from the study that the production of gum-butea can be enhanced by adopting proper depth and length of knotching which, inturn will improve livelihood of peoples inhabiting in and around the forests of Bundelkhand region of Central India.